2021
DOI: 10.1088/1361-6498/ac125a
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic follow-up studies on humans with internal and external exposure to ionizing radiation

Abstract: Cells exposed to ionizing radiation have a wide spectrum of DNA lesions that include DNA single-strand breaks, DNA double-strand breaks (DSBs), oxidative base damage and DNA-protein crosslinks. Among them, DSB is the most critical lesion, which when mis-repaired leads to unstable and stable chromosome aberrations. Currently, chromosome aberration analysis is the preferred method for biological monitoring of radiation-exposed humans. Stable chromosome aberrations, such as inversions and balanced translocations,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 100 publications
0
4
0
Order By: Relevance
“…Therefore, on-site training is currently preferred, though there may be room for improvement in on-line training to enhance its accuracy and efficiency. Balajee et al (2021) considered the cytogenetic markers that can be used in the biological monitoring of radiation-exposed humans. The classic approach is to score dicentric chromosome aberrations in peripheral blood lymphocytes but scoring of translocations (involving the exchange of fragments between two or more chromosomes) can also be useful, bearing in mind that reciprocal translocations can arise spontaneously, and their baseline frequency appears to be modulated by confounding factors such as age and lifestyle.…”
Section: Approaches To Triagementioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, on-site training is currently preferred, though there may be room for improvement in on-line training to enhance its accuracy and efficiency. Balajee et al (2021) considered the cytogenetic markers that can be used in the biological monitoring of radiation-exposed humans. The classic approach is to score dicentric chromosome aberrations in peripheral blood lymphocytes but scoring of translocations (involving the exchange of fragments between two or more chromosomes) can also be useful, bearing in mind that reciprocal translocations can arise spontaneously, and their baseline frequency appears to be modulated by confounding factors such as age and lifestyle.…”
Section: Approaches To Triagementioning
confidence: 99%
“…Although scoring of dicentrics and translocations remains the mainstay of cytogenetic dosimetry, other markers can also be used. Balajee et al (2021) identified the Pseudo Pelger-Huet (PH) anomaly as a useful marker. PH cells are a subset of neutrophils that are characterised by a bilobed nucleus connected by a thin chromatin filament.…”
Section: Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of low dose radiation exposures, cancer, cardiovascular disease, foetal abnormality, and chronic fatigue are examples of gross adverse effects [ 89 ]. These are thought to result from genomic instability, mutation in critical genes, microenvironment alterations leading to niche compromise, haematological insufficiency and immune dysfunction [ 7 , 29 , 90 , 91 , 92 , 93 , 94 , 95 , 96 ]. These in turn are attributed to DNA damage, elevated ROS, mitochondrial insufficiency, membrane channel imbalances and failure of “checks and balances” on the rate of specific enzyme reactions, leading to tipping points where metabolic malfunction occurs.…”
Section: Downstream Events—the Role Of Ribe and Rigimentioning
confidence: 99%